The Role of Lesson Study in Guiding Implementation of Learning in Elementary School - Syamsun, Muhammad; Hastuti, Wiwik Dwi; Sunandar, Asep; Hitipeuw, Imanuel; Indreswari, Henny; Ediyanto, Ediyanto (Jurnal Pendidikan Ilmu Sosial, 2022)
The aim of this Lesson Study was to improve teacher professionalism, so Lesson Study becomes one of alternative solutions in learning. Improving the quality of education must be made to achieve national education goals. Literature review and observation result about implementation of learning in the class as a method that used in this article. Lesson Study (LS) is the development of the teaching profession through the study of collaborative and sustainable learning based on the principles of collegiality and mutual learning to build learning community. Lesson Study provides a process to collaborate and design lesson and evaluate strategic success. Teaching strategy that already implemented as an effort to improve process and students’ learning gains. Teacher cooperates to plan, teach, and observe the learning that is developed cooperatively. This article will discuss related to its history, until the steps of its implementation.